Karl Polanyi the limits of the market - Dale, Gareth (Cambridge Polity Press, 2010)
Karl Polanyi's The Great Transformation is generally acclaimed as being among the most influential works of economic history in the twentieth century, and remains as vital in the current historical conjuncture as it was in his own. In its critique of nineteenth-century "market fundamentalism" it reads as a warning to our own neoliberal age, and is widely touted as a prophetic guidebook for those who aspire to understand the causes and dynamics of global economic turbulence at the end of the 2000s.
Includes bibliographical references (p. [277]-304) and index.
Keywords: Polanyi, Karl, 1886-1964.